The composition of cuticular compounds indicates body parts, sex and age in the model butterfly Bicyclus anynana (Lepidoptera) - Heuskin, Stéphanie; Vanderplanck, Maryse; Bacquet, Paul; Holveck, Marie-Jeanne; Kaltenpoth, Martin; Engl, Tobias; Pels, Christophe; Taverne, Cédric; Lognay, Georges; Nieberding, Caroline M. (Frontiers in Ecology and Evolution, 2014)
Chemical communication in insects’ sexual interactions is well-known to involve olfaction of volatile compounds called sex pheromones. In theory, sexual chemical communication may also involve chemicals with low or no volatility exchanged during precopulatory gustatory contacts. Yet, knowledge on this latter type of chemicals is so far mostly restricted to the Drosophila fly model. Here we provide the most comprehensive characterization to date of the cuticular chemical profile, including both volatile and non-volatile compounds, of a model butterfly, Bicyclus anynana. First, we characterized the body distribution of 103 cuticular lipids, mostly alkanes and methyl-branched alkanes, by gas chromatography coupled to mass spectrometry (GC-MS). Second, we developed a multivariate statistical approach to cope with such complex chemical profiles and showed that variation in the presence or abundance of a subset of the cuticular lipids indicated body parts, and traits involved in B. anynana mate choice, namely sex and age. Third, we identified the chemical structure of the 20 most indicative compounds, which were on average more abundant (1346.4 ± 1994.6 ng; mean ± SD) than other, likely less indicative, compounds (225.9 ± 507.2 ng; mean ± SD). Fourth, we showed that wings and legs displayed most of the chemical information found on the entire body of the butterflies. Fifth, we showed that non-random gustatory contacts occurred between specific male and female body parts during courtship. The body parts mostly touched by the conspecific displayed the largest between-sex differentiation in cuticular composition. Altogether, the large diversity of cuticular lipids in B. anynana, which exceeds the one of Drosophila flies, and its non-random distribution and evaluation across individuals, together suggest that gustatory information is likely exchanged during sexual interactions in Lepidoptera.